Effects of office environment on employee satisfaction: a new analysis. Issue 1 (2nd January 2016) - Leder, Solange; Newsham, Guy R.; Veitch, Jennifer A.; Mancini, Sandra; Charles, Kate E.
Abstract : Two large and detailed field studies of the effect of office environment parameters on aspects of environmental and job satisfaction were conducted. The first study focused on open-plan offices in nine conventional buildings, whereas the second encompassed open-plan and private offices in 24 buildings (12 green and 12 conventional). The data collection for these studies was separated by approximately a decade, but the data collection methods, contexts and analysis procedures were very similar. This offered the opportunity to compare the results of the studies at the workstation level, with the goal of identifying parameters consistent in affecting occupant satisfaction, and of exploring the effects of office type (open-plan versus private) and building type (green versus conventional). Satisfaction with acoustics and privacy was most strongly affected by workstation size and office type; satisfaction with lighting was most strongly affected by window access and glare conditions; and satisfaction with ventilation and temperature was most strongly affected by pollutant concentration. Occupants of green buildings rated all aspects of environmental satisfaction more highly. Finally, job satisfaction was most strongly affected by pollutant concentration and office type.